The Importance of Social Value in the Evaluation of Web Services in the Public Sector. (27th September 2015) - Lee, Sunghwan; Park, Sangun; Kim, Wooju
Wireless sensor networks (WSNs) are widely used in many different fields. Even in the public sector, various services using WSN are offered. One of the key issues is how to control and manage heterogeneous devices of WSN devices. Devices Profile for Web Services (DPWS), a standard of Web services, has been adopted to solve the problems of interoperability between WSN devices. In order to evaluate WSN services in the public sector, this paper presents a method to evaluate Web services, a base technology of sensor network services. This paper presents a value analysis methodology assessing tangible and intangible benefits of Web services in the public sector. We classify stakeholders of Web services as a government, citizens, and agents (businesses) and selected the metrics for each stakeholder's benefit. After that, we determine the weight of each metric through AHP. The result shows that social value was the most important benefit in the construction of Web services in the public sector. We expect that the main contribution of this paper is the development of a value assessment framework that reflects the unique characteristics of Web services in the public sector.